CORRELATION PATTERN OF FACTORS RELATED TO DOMESTIC VIOLENCE AGAINST MARRIED WOMEN IN TEHRAN-IRAN - Mohammadi, Maryam; Ramezankhani, Ali; Mehri, Ali; Mohammadi, Shabnam; Hashemian, Masoumeh; Khodakarim, Soheila; Golshanizaman, Neda (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the correlation pattern of factors related to domestic violence against married women in Tehran. Methodology: This descriptive study was conducted on married women in Tehran City of Iran. Subjects were selected with convenience sampling. The data collection tool was a questionnaire. The sample consisted of 554 married women, aged 18 to 66 years. Description and analysis of the data were performed using SPSS 16. Pearson correlation test and regression analysis were performed. P value <0.05 was considered significant. Results: Verbal violence (20.75%) was found to be the most common type of violence among married women followed by emotional violence (19.5%). Regarding the pattern of factors related to domestic violence, social characteristics had the highest direct effect on violence (0.288) and economic problems had the strongest overall effect (0.399) on violence. Conclusion: Verbal violence was found to be the most common type of violence among married women and economic problems had the strongest overall effect on violence.